Shifting the Value of Experience - Michael T Lai; Hsien-Hui Tang (Cubic Journal)
This paper is a reflection of the evolution of a user experience (UX) consultancy's transformation into a brand experience consultancy in an increasingly competitive market in China. As part of this transformation, the value of design has shifted from tactical to strategic. The authors compare and contrast the nature of experience design and experience strategy and how they are delivered to close the gap between designers and strategists. While this paper serves as a case study of one consultancy in China, the lessons, knowledge, and understanding gained are applicable to the user experience industry and global design community at large.